State/nation/transnation : perspectives on transnationalism in the Asia-Pacific - Yeoh, Brenda S. A.; Willis, Katie, 1968- (London ; New York : Routledge, 2004)
Setting the book within a theoretical framework, the authors explore a range of themes such as migration, identity and citizenship in chapters on China, the Philippines, Malaysia, Vietnam, Japan, Indonesia, Australia, Singapore and Cambodia.
1. Introduction : transnationalism as a challenge to the nation / Katie Willis, Brenda S.A. Yeoh and S.M. Abdul Khader Fakhri -- 2. The myth of the controllability of difference : labour migration, transnational communities and state strategies in the Asia-Pacific region / Stephen Castles -- 3. Spheres of speculation and middling transnational migrants : Chinese Indonesians in the Asia-Pacific / Donald M. Nonini -- 4. Citizenship and differential exclusion of immigrants in Japan / Keiko Yamanaka -- 5. Is there a transnation? : migrancy and the national homeland among overseas Filipinos / Filomeno V. Aguilar Jr. -- 6. Expatriating is patriotic? : the discourse on "new migrants" in the People's Republic of China and identity construction among recent migrants from the PRC / Pál Nyíri -- 7. From nation to networks and back again : transnationalism, class and national identity in Malaysia / Tim Bunnell -- 8. Indian information technology professionals' world system : the nation and the transnation in individuals' migration strategies / Xiang Biao -- 9. Beyond transnational nationalism : questioning the borders of the Chinese diaspora in the global city / Ien Ang -- 10. Democracy, culture and the politics of gate-keeping in Cambodia : the transnation goes home / Caroline Hughes -- 11. Internal transnationalism and the formation of the Vietnamese diaspora / Andrew Hardy -- 12. Shifting the axis : feminism and the transnational imaginary / Vera Mackie.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Transnationalism; Foreign workers -- Asia; Foreign workers -- Pacific Area; Asians -- Foreign countries; Asia -- Emigration and immigration; Pacific Area -- Emigration and immigration; Asian diaspora; Transnationalisme; Asiatiques -- Pays étrangers.; Asie -- Émigration et immigration; Pacifique, Région du -- Émigration et immigration; Travailleurs étrangers -- Asie; Travailleurs étrangers -- Pacifique, Région du; SOCIAL SCIENCE -- Emigration & Immigration; Emigration and immigration; Foreign workers; Transnationalism; Asia; Pacific Area